2012
DOI: 10.1186/1749-8546-7-26
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory activities of selected medicinal plants and fungi containing phenolic and flavonoid compounds

Abstract: BackgroundThis study aims to determine the relationship between the antioxidant and anti-inflammatory activities of the thirteen herbs and two fungi extracts, and their total phenolic and flavonoid contents.MethodsAntioxidant activities were evaluated by four assays: an antioxidant activity assay using Saccharomyces cerevisiae, a DPPH ((2, 2-diphenyl-1-picrylhydrazyl) assay to assess free radical scavenging, an assay assessing ferrous ions or iron (II) chelating ability, and a ferric reducing antioxidant power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 35 publications
3
85
2
3
Order By: Relevance
“…Tannins, which have potent antioxidants and anti-inflammatory activities, have been reported to reduce the levels of lipid peroxide in liver cells and thus, prevent hepatocytes from the destructive effects [23]. Phenolic compounds were also reported as the important active ingredients of natural products that are responsible for the antioxidant effect [24][25][26][27]. Findings from our phytochemical analysis showed that the water extracts of CS contained phenolic compounds and tannins.…”
Section: Discussionmentioning
confidence: 71%
“…Tannins, which have potent antioxidants and anti-inflammatory activities, have been reported to reduce the levels of lipid peroxide in liver cells and thus, prevent hepatocytes from the destructive effects [23]. Phenolic compounds were also reported as the important active ingredients of natural products that are responsible for the antioxidant effect [24][25][26][27]. Findings from our phytochemical analysis showed that the water extracts of CS contained phenolic compounds and tannins.…”
Section: Discussionmentioning
confidence: 71%
“…Comparatively, all analyzed species displayed higher reducing power than the edible fruits of Physalis alkekengi (IC 50 = 36.58 mg mL -1 ) (Diaz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is already reported that hydroxyl functionality is an integral part of most of the phenolics such as flavonoids and tannins. 38 Moreover, recent studies also show that sev- eral plant products, including polyphenolic substances (e.g., flavonoids and tannins) and various herbal extracts, show antioxidant [39][40][41][42] and antiinflammatory activities. 42 Our results revealed that the extract contains various bioactive functional groups, viz.…”
Section: Resultsmentioning
confidence: 99%